2021
DOI: 10.21548/42-1-4336
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Cork-Closed Bottle-Fermented Sparkling Wines

Abstract: Bottle fermented sparkling wine in South Africa is known as Méthode Cap Classique which is based on the method used in France for Champagne. The use of cork, instead of a crown cap during the second fermentation in sparkling wine was investigated for its effect on the phenolic profile of wines. Phenolic acids susceptible to migration from cork into wine were studied in two-disc corks from three different commercial suppliers, coded as Cork A, Cork R and Cork C and a crown cap closure. Gallic, caftaric, caffeic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
2
1
Order By: Relevance
“…The gallic acid concentration in the sparkling wines after 3 months of autolysis varied from 0.76 mg L −1 for NM to 1.53 mg L −1 in M72, whereas after 18 months of autolysis, it ranged from 3.78 mg L −1 in NM to 4.26 mg L −1 in the sparkling wine M72. These results are lower than those reported in South African sparkling wines (14.86 at 16.18 mg L −1 ) (Minnaar et al 2021 ). However, they are consistent with studies that showed an increase in concentration of the hydroxybenzoic acids, principally gallic acid in red Syrah wines elaborated with cold pre-fermentative maceration (Cejudo-Bastante et al 2014 ) and during the autolysis of sparkling wines made from other cultivars (Sartor et al 2019a ), probably due to the hydrolysis of tannins (Garrido and Borges 2013 ).…”
Section: Resultscontrasting
confidence: 73%
“…The gallic acid concentration in the sparkling wines after 3 months of autolysis varied from 0.76 mg L −1 for NM to 1.53 mg L −1 in M72, whereas after 18 months of autolysis, it ranged from 3.78 mg L −1 in NM to 4.26 mg L −1 in the sparkling wine M72. These results are lower than those reported in South African sparkling wines (14.86 at 16.18 mg L −1 ) (Minnaar et al 2021 ). However, they are consistent with studies that showed an increase in concentration of the hydroxybenzoic acids, principally gallic acid in red Syrah wines elaborated with cold pre-fermentative maceration (Cejudo-Bastante et al 2014 ) and during the autolysis of sparkling wines made from other cultivars (Sartor et al 2019a ), probably due to the hydrolysis of tannins (Garrido and Borges 2013 ).…”
Section: Resultscontrasting
confidence: 73%
“…Therefore, it is important to understand the possible impact these compounds may have on the evolution of wine sealed with cork stoppers. A recent study showed that corks from different origins (suppliers) could impact differently on wine properties [ 79 ] due to the phenolic acids susceptible to passing from cork to wine. Gallic, caftaric, caffeic, and p -coumaric acids were studied in two-disc corks from three different commercial suppliers.…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid was significantly higher in Cork A wines, which indicates the contribution of Cork A to the concentration of this compound in the wine. This may be due to differences in the surface roughness of cork that would increase the surface area in contact with the wine [ 79 ]. Moreover, a study evaluated the reactivity of phenolic compounds from cork stoppers and assayed their reaction with two major wine components, namely, (+)-catechin, and malvidin-3- O -glucoside.…”
Section: Introductionmentioning
confidence: 99%